Analysis of the AAP Valencia nº 276/2019 of 11 October: international jurisdiction clause included in the bill of lading regime: subrogation of one of the parties - Romero Matute, Yeray (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
In this article, following the Spanish Order nº 276/2019 of 11 October 2019, it will be analyzed the reasons that brought a Spanish company to bring a lawsuit against another Spanish company and its own insurer –for a supposed failure to carry out a transport contract based on a bill of lading– in the Spanish Courts, using the general forum of the domicile of the defendant according to article 4 of Regulation (EU) nº 1215/2012. The defendant, requested an international declinatory in response to such a claim. However –as can be seen in this case–, it was the plaintiff who attempted to avoid a clause of express submission to the London courts contained in that agreement.
Keywords: bill of lading; passive legitimation; submission clause; international declinatory